SalA Attenuates Hypoxia-Induced Endothelial Endoplasmic Reticulum Stress and Apoptosis via Down-Regulation of VLDL Receptor Expression - Ping Xie; Yingchun Duan; Xianzhi Guo; Lina Hu; Minghua Yu (Cellular Physiology and Biochemistry, 2015)
Background: Salvianolic acid A (SalA) has been shown to display robust protection against endothelial injury. VLDL receptor (VLDLr) is expressed at high levels in the endothelial cells. However its endothelial biological function has not been completely elucidated. Here, we investigated molecular effects of SalA on endothelial VLDLr expression, ER stress, and apoptosis under hypoxia condition. Methods: Human umbilical vein endothelial cells (HUVECs) pretreated with SalA were subjected to hypoxia stimulation. Endothelial ER stress and apoptosis were examined. The mRNA levels were tested by real-time RT-PCR, and the protein levels were determined by immunoblot analysis. Results: Pretreatment of HUVECs with SalA markedly attenuated hypoxia-induced endothelial ER stress and apoptosis. Hypoxia resulted in enhancement of VLDLr expression, which was effectively inhibited by SalA pretreatment. Furthermore, luciferase reporter gene assays indicated that SalA inhibited vldlr gene promoter activity, and ChIP assays showed that hypoxia increase the recruitment of HIF-1α to the vldlr gene promoter, and this process was hampered markedly by pretreatment of SalA. Finally, overexpression of VLDLr abolished SalA-mediated protection of endothelial cells from ER stress and apoptosis. Knockdown of VLDLr mimicked SalA protective effect. Conclusion: These results for the first time demonstrate that SalA protects against hypoxia-induced endothelial ER stress and apoptosis through inhibiting recruitment of HIF-1α to vldlr gene promoter and thus suppressing VLDLr expression.